2018
DOI: 10.6004/jnccn.2018.0072
|View full text |Cite
|
Sign up to set email alerts
|

NCCN Guidelines Insights: Bladder Cancer, Version 5.2018

Abstract: The NCCN Clinical Practice Guidelines in Oncology for Bladder Cancer provide recommendations for the diagnosis, evaluation, treatment, and follow-up of patients with bladder cancer. These NCCN Guidelines Insights discuss important updates to the 2018 version of the guidelines, including implications of the 8th edition of the AJCC Cancer Staging Manual on treatment of muscle-invasive bladder cancer and incorporating newly approved immune checkpoint inhibitor therapies into treatment options for patients with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 191 publications
(178 citation statements)
references
References 35 publications
4
166
0
8
Order By: Relevance
“…2 However, despite these challenges, clinical staging of bladder cancer is defined by the American Joint Committee on Cancer staging system and is incorporated into practice guidelines. [16][17][18] We have demonstrated the impact of pDS on OS in 2 highly complementary data sets representing the full spectrum of real-world clinical practice environments and have highlighted the utility of this endpoint despite the aforementioned complexities. Furthermore, notwithstanding the potential difficulties of clinical staging applicable to all patients with MIBC, we have demonstrated a significantly higher likelihood of achieving pDS with NAC in comparison with cystectomy alone.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, despite these challenges, clinical staging of bladder cancer is defined by the American Joint Committee on Cancer staging system and is incorporated into practice guidelines. [16][17][18] We have demonstrated the impact of pDS on OS in 2 highly complementary data sets representing the full spectrum of real-world clinical practice environments and have highlighted the utility of this endpoint despite the aforementioned complexities. Furthermore, notwithstanding the potential difficulties of clinical staging applicable to all patients with MIBC, we have demonstrated a significantly higher likelihood of achieving pDS with NAC in comparison with cystectomy alone.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies on BCG refractory and BCG relapsing, patients with BCG‐unresponsive disease are extremely unlikely to benefit from further conservative therapy, including repeated BCG therapy . In this category, the National Comprehensive Cancer Network and European Association of Urology guidelines presented therapeutic options for RC, another intravesical immunotherapy, intravesical chemotherapy, device‐assisted therapy, combination chemoimmunotherapy, gene therapy and participation in a clinical trial; however, further investigations and validation are warranted for these alternative conservative therapies . Although early RC is regarded as the preferred option for patients with BCG‐unresponsive disease, a notable subset of patients want to preserve their bladders or are not suitable candidates for radical surgery.…”
Section: Subclassification Of Bcg Failure and The Definition Of Bcg‐umentioning
confidence: 99%
“…27 In this category, the National Comprehensive Cancer Network and European Association of Urology guidelines presented therapeutic options for RC, another intravesical immunotherapy, intravesical chemotherapy, device-assisted therapy, combination chemoimmunotherapy, gene therapy and participation in a clinical trial; however, further investigations and validation are warranted for these alternative conservative therapies. 1,28 Although early RC is regarded as the preferred option for patients with BCG-unresponsive disease, a notable subset of patients want to preserve their bladders or are not suitable candidates for radical surgery. Therefore, patients in this category are now regarded as good candidates for a single-arm clinical trial, because an appropriate control does not exist, and several trials are now ongoing worldwide, as discussed later.…”
Section: Concept For "Bcg Unresponsive"mentioning
confidence: 99%
“…RC entails high risk of re‐operations, long hospital‐stays, long‐term sequelae, and even postoperative mortality . A contemporary bladder‐sparing treatment alternative to RC is chemoradiotherapy . There is no evidence from randomized controlled trials to support superiority of RC over radiotherapy with respect to survival.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 A contemporary bladder-sparing treatment alternative to RC is chemoradiotherapy. [5][6][7][8] There is no evidence from randomized controlled trials to support superiority of RC over radiotherapy with respect to survival. The largest trial to date was closed due to poor accrual, 9 and a recent review concluded that observational studies comparing outcomes of RC to bladder-sparing therapies had serious methodological shortcomings and inconsistent findings.…”
Section: Introductionmentioning
confidence: 99%